Development of Consciousness: from Limited to Unlimited - Galstyan, Armenuhi (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
Consciousness becomes partially visible through some content, and only an empty consciousness manifests itself in its infinity. Consciousness is seen in the body through behavioral activity, consciousness outside the body is reachable through spiritual experience and transpersonal experiences. A person with a personal consciousness acts under conditions of the limitedness of the created internal and external factors. Transpersonal consciousness is access to the true or divine nature, to hidden possibilities and infinity. Personal consciousness can reject effective development, transpersonal consciousness allows to control normal and productive development by controlling the content of personal consciousness and using transpersonal experience. The instinctive level of the unconscious is equivalent to the lower layers of consciousness. The equivalent of the upper level of consciousness are the symbols of the unconscious. Comparing the mental product of the conscious and unconscious can determine internal conflicts and the degree of harmony. Transpersonal logic or “the logic of the whole” sheds light on conscious or unconscious problems contributing to their solution or transformation. Transpersonal experience and transcendental experiences can be generated through meditation and concentration of attention.
Keywords: consciousness, personal consciousness, transpersonal consciousness, transpersonal experience, a layer of consciousness, the development of consciousness, content, the unconscious, the logic of the whole, meditation